Peningkatan Keaktifan Peserta Didik Kelas 1B di SDN Jajar Tunggal III/452 Surabaya pada Materi Operasi Hitung Pengurangan menggunakan Media Puzzle Math - Dhiya Haniffasary; Meilantifa Meilantifa; Ida Nur Azizah (Lembaga Pengembangan Kinerja Dosen, 2024)
The low level of student activity in their numeracy skills is a problem in the Mathematics learning process. Research conducted at SDN Jajar Tunggal III/452 Surabaya showed the results that interactive media in learning was very influential in the students' learning process. The use of Puzzle Math interactive media aims to increase the activity of class 1 students who are in the transition phase from PAUD to play while playing. The data collection technique uses the Classroom Action Research (PTK) method which is carried out in 2 cycles, from the results of observations, written tests and student activity during the learning process.